1994
DOI: 10.1002/cne.903450104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mu opioid receptor mRNA in rat brain: An in situ hybridization study at the single cell level

Abstract: The mu (mu) opioid receptors, which mediate the effects of morphine, are widely distributed in brain. We have examined the distribution of mRNA encoding a mu opioid receptor in rat brain with in situ hybridization histochemistry at the single-cell level to obtain information about the cell types synthesizing this receptor. Only neurons, not glia, were labeled in discrete brain regions. High levels of labeling were detected in the thalamus, striosomes of the caudate-putamen, globus pallidus, and brain regions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
115
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 60 publications
(85 reference statements)
14
115
0
1
Order By: Relevance
“…Analysis of film autoradiograph revealed that m-opioid receptor mRNA exhibited low constitutive expression in the VTA of control rats, in agreement with previously described low basal m-opioid receptor mRNA expression in rat VTA (Mansour et al, 1994;Delfs et al, 1994). The autoradigraphic density of m-opioid receptor mRNA labeling significantly increased after repeated social defeat stress.…”
Section: L-opioid Receptor Mrna Expression Is Upregulated After Repeasupporting
confidence: 89%
“…Analysis of film autoradiograph revealed that m-opioid receptor mRNA exhibited low constitutive expression in the VTA of control rats, in agreement with previously described low basal m-opioid receptor mRNA expression in rat VTA (Mansour et al, 1994;Delfs et al, 1994). The autoradigraphic density of m-opioid receptor mRNA labeling significantly increased after repeated social defeat stress.…”
Section: L-opioid Receptor Mrna Expression Is Upregulated After Repeasupporting
confidence: 89%
“…Though the exact mechanism is unknown, IC outputs chronically regulate detection thresholds for painful stimuli in the periphery via GABAergic signais (Jasmin et al, 2003;Jasmin et aL, 2004). In addition, an unusually dense staining region for ~-opioid receptors (primary receptor targets for analgesia-producing opiates such as morphine) is present in the rostral agranular region (Delfs et aL, 1994;Burkey et aL, 1996). Of interest here, the IC is connected with other structures involved in TLE, such as the anterior hippocampus, the PC and the amygdala.…”
Section: Extrahippocampal Involvement In Tle: the Insular Cortexmentioning
confidence: 95%
“…4AP application results in downregulation of the KCC2 co-transporter in hippocampal slices, resulting in intracellular CI-accumulation and hence depolarizing postsynaptic responses to GABA (Rivera et aL, 2004). It is thus possible that these potentials were not completely abolished despite the presence of DAGO due to strong somatic excitation mediated by interneuron recurrent collateral release of depolarizing GABA, to lead to large synchronized interneuronal network discharges (Michelson and Wong, 1994 (Delfs et aL, 1994;Burkey et aL, 1996;Jasmin et aL, 2003). The increased abundance of IJ-opioid receptors within the IC therefore may account for differences in response to DAGO between the PC and the IC, however more experimentation would be necessary to determine precisely how these phenomena relate.…”
Section: ~-Opioid Receptor Modulation Of Synchronous Glutamate-indepementioning
confidence: 99%
“…Conversely, THC withdrawal symptoms were significantly reduced in enkephalin-deficient animals . The expression of opioid and cannabinoid receptors overlaps in many brain areas, including structures of the reward circuitry (Herkenham, 1992;Matsuda et al, 1993;Delfs et al, 1994;Mansour et al, 1995a,b). Although colocalization studies with cellular resolution have not been performed yet, it has been suggested that both receptor types may interact at the level of signal transduction .…”
mentioning
confidence: 99%